2010
DOI: 10.4137/cmt.s1993
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of Inflammatory and Pruritic Manifestations of Corticosteroid-Responsive Dermatoses Focus on Clobetasol Propionate

Abstract: Clobetasol-17 propionate is a dihalogenated corticosteroid which, on the basis of the vasoconstrictor assay, is classified as the most potent of all topical steroids. Since 1973 it has been marketed specifically for the short term topical treatment of moderate and severe cortico-responsive dermatoses for its antinflammatory, immunosuppressive and antimitotic effects. Psoriasis, atopic dermatitis, chronic eczema, boullous disorders and itching dermatosis of the genital area are usually well controlled by clobet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…It can be used alone or with other topical agents if required to induce a rapid clearing of skin lesions in inflammatory dermatoses. 5 Two pivotal randomized controlled trials and a maximal use safety study have demonstrated efficacy, skin tolerability, and safety of CP 0.025% cream. 3 A randomized, multi-center, open-label study compared the plasma concentrations of CP before and after 2 weeks of topical treatment with either CP 0.05% or CP 0.025% cream.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used alone or with other topical agents if required to induce a rapid clearing of skin lesions in inflammatory dermatoses. 5 Two pivotal randomized controlled trials and a maximal use safety study have demonstrated efficacy, skin tolerability, and safety of CP 0.025% cream. 3 A randomized, multi-center, open-label study compared the plasma concentrations of CP before and after 2 weeks of topical treatment with either CP 0.05% or CP 0.025% cream.…”
Section: Discussionmentioning
confidence: 99%
“…6 Moreover, the 0.025% CP formulation has demonstrated proven efficacy in many other chronic skin diseases, including controlling inflammation and pruritus in various steroidresponsive dermatoses. 2 CP is a highly potent fifthgeneration corticosteroid recommended for the treatment of psoriasis and other corticosteroid-responsive dermatoses. 1,2 Two independent 15-day phase III, randomized, controlled trials demonstrated significantly better primary and secondary endpoint success using CP, 0.025% cream formulation in patients with moderate-to-severe plaque psoriasis compared to the vehicle cream (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…2 CP is a highly potent fifthgeneration corticosteroid recommended for the treatment of psoriasis and other corticosteroid-responsive dermatoses. 1,2 Two independent 15-day phase III, randomized, controlled trials demonstrated significantly better primary and secondary endpoint success using CP, 0.025% cream formulation in patients with moderate-to-severe plaque psoriasis compared to the vehicle cream (p<0.001). 1 CP cream, 0.025% significantly reduces body surface area and shows clear or almost clear skin at the end of the 15day treatment in a high percentage of patients with moderate-to-severe plaque psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 CP is a fifth-generation corticosteroid and is considered the most potent topical steroid. 3 The new CP 0.025% cream formulation has been approved to be applied twice daily for the treatment of moderate-to-severe psoriasis in adult patients. CP 0.025% cream does not contain known contact allergens, such as propylene glycol, short-chain alcohols, and sorbitol-based emulsifiers, unlike the previous CP formulations (0.05%).…”
Section: Introductionmentioning
confidence: 99%